Potential plasma biomarkers at low altitude for prediction of acute mountain sickness - Guo, Haoran; Wang, Qi; Li, Tao; Chen, Jingwen; Zhang, Chao; Xu, Ying; Chang, Qing; Li, Hangyi; Sun, Weiqiang; Han, Ruidi; Wang, Chi; Wang, Chengbin (Frontiers in Immunology, 2023)
Background: Ascending to high altitude can induce a range of physiological and molecular alterations, rendering a proportion of lowlanders unacclimatized. The prediction of acute mountain sickness (AMS) prior to ascent to high altitude remains elusive.Methods: A total of 40 participants were enrolled for our study in the discovery cohort, and plasma samples were collected from all individuals. The subjects were divided into severe AMS-susceptible (sAMS) group, moderate AMS-susceptible (mAMS) group and non-AMS group based on the Lake Louise Score (LLS) at both 5000m and 3700m. Proteomic analysis was conducted on a cohort of 40 individuals to elucidate differentially expressed proteins (DEPs) and associated pathways between AMS-susceptible group and AMS-resistant group at low altitude (1400m) and middle high-altitude (3700m). Subsequently, a validation cohort consisting of 118 individuals was enrolled. The plasma concentration of selected DEPs were quantified using ELISA. Comparative analyses of DEPs among different groups in validation cohort were performed, followed by Receiver Operating Characteristic (ROC) analysis to evaluate the predictive efficiency of DEPs for the occurrence of AMS.The occurrence of the AMS symptoms and LLS differed significantly among the three groups in the discovery cohort (p<0.05), as well as in the validation cohort.Comparison of plasma protein profiles using GO analysis revealed that DEPs were primarily enriched in granulocyte activation, neutrophil mediated immunity, and humoral immune response. The comparison of potential biomarkers between the sAMS group and non-AMS group at low altitude revealed statistically higher levels of AAT, SAP and LTF in sAMS group (p=0.01), with a combined area under the curve(AUC) of 0.965. Compared to the mAMS group at low altitude, both SAP and LTF were found to be significantly elevated in the sAMS group, with a combined AUC of 0.887. HSP90-α and SAP exhibited statistically higher levels in the mAMS group compared to the non-AMS group at low altitude, with a combined AUC of 0.874.Inflammatory and immune related biological processes were significantly different between AMS-susceptible and AMS-resistant groups at low altitude and middle high-altitude. SAP, AAT, LTF and HSP90-α were considered as potential biomarkers for the prediction of AMS at low altitude.